2020
DOI: 10.1126/science.aax6089
|View full text |Cite
|
Sign up to set email alerts
|

Golgi-derived PI ( 4 ) P-containing vesicles drive late steps of mitochondrial division

Abstract: Mitochondrial plasticity is a key regulator of cell fate decisions. Mitochondrial division involves Dynamin-related protein-1 (Drp1) oligomerization, which constricts membranes at endoplasmic reticulum (ER) contact sites. The mechanisms driving the final steps of mitochondrial division are still unclear. Here, we found that microdomains of phosphatidylinositol 4-phosphate [PI(4)P] on trans-Golgi network (TGN) vesicles were recruited to mitochondria–ER contact sites and could drive mitochondrial division downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(187 citation statements)
references
References 40 publications
6
158
1
2
Order By: Relevance
“…In mammals, four receptors recruit cytosolic DRP1 to the mitochondrial outer membrane: mitochondrial fission factor (MFF), mitochondrial dynamics proteins of 49 and 51 kDa (MID49 and MID51; encoded by Mief2 and Mief1, respectively), and mitochondrial fission 1 (FIS1) (Chan, 2012). Dynamin-2 (DNM2) has been proposed to act at a terminal step following DRP1 constriction (Lee et al, 2016), but this idea was recently challenged (Fonseca et al, 2019;Kamerkar et al, 2018;Nagashima et al, 2020). Lysosomes (Wong et al, 2018) and Golgi-derived vesicles (Nagashima et al, 2020) have also been implicated in mitochondrial fission, but how they interact with the fission machinery remains to be resolved.…”
Section: Mitochondrial Dynamics At a Glancementioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, four receptors recruit cytosolic DRP1 to the mitochondrial outer membrane: mitochondrial fission factor (MFF), mitochondrial dynamics proteins of 49 and 51 kDa (MID49 and MID51; encoded by Mief2 and Mief1, respectively), and mitochondrial fission 1 (FIS1) (Chan, 2012). Dynamin-2 (DNM2) has been proposed to act at a terminal step following DRP1 constriction (Lee et al, 2016), but this idea was recently challenged (Fonseca et al, 2019;Kamerkar et al, 2018;Nagashima et al, 2020). Lysosomes (Wong et al, 2018) and Golgi-derived vesicles (Nagashima et al, 2020) have also been implicated in mitochondrial fission, but how they interact with the fission machinery remains to be resolved.…”
Section: Mitochondrial Dynamics At a Glancementioning
confidence: 99%
“…Dynamin-2 (DNM2) has been proposed to act at a terminal step following DRP1 constriction (Lee et al, 2016), but this idea was recently challenged (Fonseca et al, 2019;Kamerkar et al, 2018;Nagashima et al, 2020). Lysosomes (Wong et al, 2018) and Golgi-derived vesicles (Nagashima et al, 2020) have also been implicated in mitochondrial fission, but how they interact with the fission machinery remains to be resolved.…”
Section: Mitochondrial Dynamics At a Glancementioning
confidence: 99%
“…PI(4)P is one of the most abundant phosphoinositides, which is usually concentrated in the trans-Golgi network [ 35 ]; thus, the mechanism by which PI(4)P may influence mitochondrial dynamics is not immediately obvious. However, while this manuscript was in preparation, Nagashima and colleagues reported that Golgi-derived PI(4)P-containing vesicles were required for the final stages of mitochondrial fission [ 3 ]. In that study, the authors found that loss of PI(4)KIIIβ led to hyperfusion and increased branching of the mitochondrial network, consistent with what we observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining an appropriate balance of fission and fusion, as well as transport dynamics, is crucial for cellular health and survival as mutations in many of the core components cause severe neurological conditions in humans and model organisms [ 2 ]. Recently, a role for phosphatidylinositol 4-phosphate [PI(4)P] in mitochondrial fission has been elucidated in cultured cells [ 3 ], but the in vivo consequences have not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…PI(4)KIIIβ is also involved in the recruitment of the small G protein Rab11a [174,175] shown to be important for tsVSV-G trafficking from the trans-Golgi to the plasma membrane [176]. PI(4)KIIIβ was shown to have an important role in mitochondrial scission generating PI(4)P on trans-Golgi derived vesicles after recruitment by Arf1 [177]. These vesicles are targeted to mitochondria-ER contact sites and are thought to drive mitochondrial division downstream of Drp1 (Dynamin-related protein-1).…”
Section: Pi(4)kiiiβmentioning
confidence: 99%